Health Education to Overcome Side Effects of Chemotherapy in Cancer Patients - Sukmawati Sukmawati; Lilis Mamuroh; Furkon Nurhakim (ABDIMAS: Jurnal Pengabdian Masyarakat, 2023)
Cancer is a chronic disease that requires treatment for a long time and is a priority cause of death in developing countries. One of the cancer treatments is chemotherapy, which can cause several side effects that often occur, including nausea, vomiting, and fever. Side effects that are not handled properly will reduce the quality of life for patients and their families. This community service aims to increase patient, family, and community knowledge about overcoming the side effects of chemotherapy in cancer patients. The method used in this community service is health education through webinars targeting cancer patients, their families, and the community. Participants who took part in this health education program were 50 participants. The activity begins with a pre-test, followed by the delivery of material and questions and answers. To find out the effectiveness of health education on the knowledge of webinar participants about how to deal with the side effects of subsequent chemotherapy, post-tests were carried out. After health education, there was an increase in knowledge; namely, before education, most participants (52%) had sufficient knowledge, with an average score of 59.35, and after health education, most participants (76%) had good knowledge, with an average score of 84. Ways to deal with the side effects of chemotherapy include distraction, relaxation, hypnosis, acupuncture, and acupressure therapeutic massages. During the health education, it appeared that the participants were very enthusiastic about participating in this activity, as evidenced by the many questions from the participants and an increase in knowledge. The results of this health education are expected to not only increase the participants' knowledge but also be applied to cancer patients who experience side effects after chemotherapy.